IMPLEMENTASI HUKUM PIDANA TERHADAP PELECEHAN SEKSUAL ANAK DI BAWAH UMUR DI ERA GENERASI MILENIAL DI WILAYAH KABUPATEN BANGKA TENGAH BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Virna Dewi (Legalita, 2022)
Criminal threats in the Child Protection Law, especially the articles on sexual harassment and sexual violence (the Child Protection Law states "committing violence to force children to have intercourse), where the minimum criminal threat and the maximum criminal threat are all the same, both harassment and sexual violence (rape). So, according to the author, if so, it means that the law considers sexual harassment to be the same as rape even though it is not, because sexual harassment is the act of someone who abuses a child, whether it's a girl or a boy, either by hugging him, kissing him, holding his injured limbs. considered taboo, the perpetrators of sexual harassment are threatened with imprisonment for a minimum of 5 (five) years and a maximum of 15 (fifteen) years. Meanwhile, if someone commits violence or forces a child to have sexual intercourse, the perpetrator is also only threatened with a minimum imprisonment of 5 (five) years and a maximum of 15 (fifteen) years, so that between perpetrators of sexual harassment and perpetrators of sexual violence the threat is the same. Meanwhile, sanctions for perpetrators of violence against children, both physical violence, psychological violence, sexual crimes, and neglect are regulated in Law Number 35 of 2014.